Agile methodologies for the digital transformation of a Colombian telecommunications company (2025)
Contemporary business dynamics drive the adoption of agile methodologies as an effective response to rapid market evolution and the need for organizational adaptability. However, implementing traditional environments faces significant challenges, especially for companies rooted in traditional practices, such as telecommunications companies in Colombia. This research project is dedicated to implementing agile methods, specifically Objectives and Key Results (OKR), in a traditional organizational context. It is recognized that challenges arise when attempting to integrate these approaches into organizational contexts that maintain practices rooted in tradition, which hinders the cultural change necessary to achieve the entity's strategic objectives. Presumably, successful implementation of OKRs must facilitate deep cultural transformation, achieve effective alignment with strategic objectives, and proactively address internal objections through engagement and communication strategies. For this purpose, we designed a methodology to implement agility in the technical transformation of a company in the TELCO sector in Colombia, considering the challenges it proposes and seeking to address them methodologically.